Integrating Technology in Teacher Education: Transforming Learning Environments in Nigerian Colleges of Education - Usman, Binta Fatima; Obisesan, Rachael Oyeranti; Ifabiyi, Albert Oluwagbenga (Faculty of Natural and Applied Sciences Journal of Computing and Applications, 2025)
The integration of technology in teacher education is crucial for transforming learning environments in Nigerian colleges of education. As the educational landscape evolves, it’s essential for teacher educators to adopt innovative methodologies that leverage technology. This paper discusses the numerous benefits of technology integration, such as enhanced teaching and learning experiences, the development of 21st-century skills, better access to resources, and increased student engagement. However, challenges remain, including inadequate infrastructure, limited resources, insufficient training programs, resistance to change, and budgetary constraints. To address these challenges, the paper proposes strategic approaches, including developing a tailored technology integration plan, continuous professional development for educators, and establishing partnerships with technology companies. Redesigning classrooms to support technology-enhanced learning and promoting student-centered approaches are also vital. The roles of stakeholders, government, private sector partners, teacher educators, and students are critical in this transformation. A collaborative effort among all stakeholders is necessary to overcome existing challenges and fully realize the benefits of technology, ultimately enhancing the quality of teacher education for the demands of the 21st century. The paper therefore, concludes that the integration of technology in teacher education has transformative potential;the government should ensure adequate infrastructure and funding, while private sector involvement can provide necessary resources. Teacher educators must lead in embracing technology, and students should actively shape their learning experiences.